Clustering Wilayah Potensi dan Strategi Pengembangan Komoditas Unggulan Tanaman Hortikultura dan Palawija Level Kecamatan di Sumatera Barat Tahun 2021 - Widyatami, Afifatul Ilma; Reistiani, Viana Mei (Seminar Nasional Official Statistics, 2023)
Food crops and horticulture are commodities that contribute the largest GRDP contribution to the agricultural sector. Labor in the agricultural sector is also still the backbone of employment in West Sumatra. Leading commodities become an important thing in the focus of a region's development to increase economic growth and people's welfare. Regional clusters of potential food crops and horticulture are needed to determine the superior commodities of a region down to the district level so that regional development can be focused on these superior commodities. The K-Means method is used because it has the advantage of being mutually independent between the clusters formed and not overlapping. At the beginning of cluster formation, the within cluster variation method was used to achieve ideal conditions, namely small variations within clusters and large variations between clusters. The potential areas for secondary crops identified are in 38 districts. As for horticultural crops, the identified potential areas are in 17 districts for seasonal fruit and vegetable plants, 14 districts for biopharmaceutical plants, 39 districts for annual fruit and vegetable plants, and 5 districts for ornamental plants. After knowing the superior commodities of a region, an assessment of the strategy for increasing production is carried out as a follow-up to determine the advancement of superior commodities in a region.